White spot syndrome virus (WSSV) recombinant envelope protein VP28 activates shrimp phagocytic activity - Htut N.W. (2023)
Diseases constitute a fundamental limiting factor for stable and reliable production of cultured shrimp. Successful vaccination against white spot syndrome virus in shrimp by using the viral recombinant envelope protein VP28 has been previously reported. We hypothesized that the mechanism of the subunit vaccine protection might be via an increase of phagocytic activity in vaccinated shrimp. To test this hypothesis, monomeric recombinant VP28 protein (rVP28) was prepared and injected into the shrimp at the concentration of 25 µg/shrimp. Then, hemolymph was collected at different as 15, 30, and 60 min post injection (p.i.) to determine the total hemocyte count (THC) and phagocytic activity. Results revealed that THC and phagocytic activity increased significantly at 30 min post injection, but that THC subsequently declined by 60 min post injection. The findings indicated that rVP28 could induce an increase in circulating hemocyte numbers and activate phagocytic activity. The data obtained provides a baseline for further work on improving vaccination efficacy for protection against white spot syndrome virus (WSSV).